VIGOUR AND a-AMYLASE ANALISIS IN SEEDS OF RICE CULTIVARS SUBMITTED TO SEVERAL TREATMENTS WITH ACETIC ACID - Neves, Luiz Augusto Salles das; Moraes, Dario Munt de (Revista de Ciências Agroveterinárias, 2005)
The organic acids accumulated due to the decomposition of organic material in soils under irrigation affect rice seedling development. For this reason, the influence of organic acids action on rice seed physiological quality must be studied. Rice seeds of cultivars BR IRGA-410 and Epagri 111 were submitted to different acetic acid concentrations (zero; 1,0; 2,0; 4,0; 8,0; and 16,0 ml.L-1) in order to evaluate the starch content and a-amylase activity in the germination and the electrical conductivity. All tests followed the completely randomized experimental design with four replications. The F test was significant for all the evaluated variables. The first germination counting (PCG) and germination (G) tests were reduced in both cultivars with the increase in acetic acid concentration. The electrical conductivity test (CE) showed that cultivar Epagri 111 released higher quantity of exsudate than BR IRGA-410. The starch solubilization (Am) decreased with the enhancement of acetic acid concentration for Epagri 111 and increased until the concentration of 4,0 ml.L-1 for BR IRGA-410, decreasing afterwards. The a-amylase activity increased with the elevation of acetic acid concentration for BR IRGA-410 and decreased for Epagri 111. The acetic acid usually affected negatively both cultivars.